Penyelesaian Perkara Menurut Ketentuan Adat Tentang Hewan Ternak Yang Masuk Ke Kebun Orang Lain: Studi Kasus Di Desa Motaulun Kecamatan Malaka Barat Kabupaten Malaka - Daniel Klau; Deddy R. CH. Manafe; Adrianus Djara Dima (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Livestock is one of the main sources of income for rural communities, especially in Motaulun Village, Malacca Regency, West Malacca District. However, livestock that are not properly cared for by the owner can cause various problems. These disputes can be resolved through various means, both formally and informally. Many people prefer to resolve this dispute informally, namely through the settlement of cases outside the court. The settlement of cases outside the trial aims to find a solution that is acceptable to the parties, without having to follow a formal judicial process. This research is an empirical research, so the data source used is the primary data source, the primary data is obtained from the results of interviews. The Empirical Method is a legal research method that functions to see the law in a real sense and research how the law works in the community. The data were analyzed in a descriptive-qualitative manner. The results of this study show that: (1) The settlement of cases according to customary provisions carried out by the people of Motaulun Village goes through several stages, namely the first is a complaint from the victim to the Motaulun Village officials, the process of summoning the parties to the dispute, deliberations led by the traditional elder Ambei Fukun, the imposition of sanctions. (2) Factors that affect the community in Motaulun Village prefer alternative settlement outside of court, namely because of the existence of customary institutions as a forum in the settlement process, public legal awareness, fast and cheap settlement, and also distance. These factors influence the community in choosing to settle cases outside the court.